2002
DOI: 10.1002/cncr.10963
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of c‐myc and AIB1 amplification in hepatocellular carcinoma

Abstract: BACKGROUNDAmplifications of 1q21, c‐myc at 8q24.1, and AIB1 at 20q12 are genetic alterations that are detected frequently in hepatocellular carcinoma (HCC). The authors evaluated the association of these amplifications with the prognosis of patients with HCC.METHODSIn the current study, amplification of 1q21, c‐myc, and AIB1 was analyzed in 560 specimens from 400 patients with HCC and 20 patients with benign liver lesions using fluorescence in situ hybridization with high‐throughput tissue microarray. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 33 publications
9
140
1
3
Order By: Relevance
“…Thus, it is reasonable to suggest that the genomic instability reflected by aneuploidy has to be followed by multiple cellular alterations in order to reach malignant properties. One of the decisive steps in this transformational process is the ability of genomically altered cells to proliferate, which is compulsory for clonal expansion (Wang et al 2002). In the present study, six out of eight UCC specimens exhibited an increased cyclin A expression pattern.…”
Section: Aneuploidy and Colorectal Cancer Risk In Ulcerative Colitissupporting
confidence: 47%
“…Thus, it is reasonable to suggest that the genomic instability reflected by aneuploidy has to be followed by multiple cellular alterations in order to reach malignant properties. One of the decisive steps in this transformational process is the ability of genomically altered cells to proliferate, which is compulsory for clonal expansion (Wang et al 2002). In the present study, six out of eight UCC specimens exhibited an increased cyclin A expression pattern.…”
Section: Aneuploidy and Colorectal Cancer Risk In Ulcerative Colitissupporting
confidence: 47%
“…26 It has also been described to be amplified in endometrial, stomach, prostate, pancreatic, and hepatocellular carcinomas. [27][28][29] NCOA3 is as transcription coactivator involved in cell proliferation, migration, differentiation, and growth. 30 Henke et al 31 could show that NCOA3 amplification seems to be an early event during pancreatic cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of MYC has been observed frequently in large HCC nodules, suggesting that it is a late genetic alteration in the progression of HCC. 24 The PTK2 gene has also been identified as a target for the amplification event at 8q23-24, and elevated expression of PTK2 is associated with a large tumor size in HCC. 25 Our data revealed that four genes were correlated with poor differentiation of HCV-HCC.…”
Section: Discussionmentioning
confidence: 99%